In vitro, modulation of the dominant intestinal microbiota in type 2 diabetics by controlling antimicrobial activity with the methanolic extract of Pistacia lentiscus L - Bourroubey, Bachir; Chelli, Nadia; Touil, Aicha Tir; Meddah, Boumediene (Acta scientiarum. Biological sciences, 2024)
The intestinal microbiota has become known as the ‘second brain’ a complementary organ for most metabolic and defensive reactions. The study aims to investigate the potential of the methanolic extract of Pistacia lentiscus leaves to modulate the dominant flora in type 2 diabetic patients compared to healthy subjects, by controlling growth kinetics. Comparative study between the dominant flora of type two diabitics (DT2) and helthy subjects (HS) stools. Using fully sterilized experimental space and materials, the germs were isolated through an antimicrobial study, and their microbial growth kinetics, were analyzed both with and without phytotherapeutic treatment in vitro. This was carried out as part of a study into the effect of methanolic extract from the leaves of the Pistacia lentiscus L. plant harvested in north-west Algeria. The study found a decrease in the quantity of lactobacilli and streptococci in DT2 and an inverse relationship between enterobacteria and streptococci in all microbiotas. On the molecular side. The methanolic extract of P lentiscus leaves gave a super antimicrobial effect for E coli and Clostridium sp at concentrations below their Minimum Inhibitory Concentration (2 mg mL-1), compared with the other gram positives studied, lactobacillus and Streptococcus (4 mg mL-1). This beneficial action confirms the high antimicrobial effect of the methanolic extract of P lentiscus leaves with lower concentration for the quantitative restauration of intestinal microbiota, the intermediary between insoluno-resistance and metabolism. Pistacia lentiscus has the potential to modulate the dominant flora in type 2 diabetics, through its regulatory antimicrobial power.